2017
DOI: 10.1016/j.jaip.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

School Environmental Intervention to Reduce Particulate Pollutant Exposures for Children with Asthma

Abstract: Background Home-based interventions to improve indoor air quality have demonstrated benefits for asthma morbidity, yet little is known about the effect of environmental interventions in the school setting. Objective We piloted the feasibility and effectiveness of a classroom-based air cleaner intervention to reduce particulate pollutants in classrooms of children with asthma. Methods In this pilot randomized controlled trial, we assessed the effect of air cleaners on indoor air particulate pollutant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 24 publications
0
65
2
Order By: Relevance
“…[5] We then piloted in a school-based setting that we could feasibly bring down asthma-based triggers in schools. [16] This utilized classroom-suitable HEPA air filters[16] specifically adapted to maximize flow while minimizing noise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] We then piloted in a school-based setting that we could feasibly bring down asthma-based triggers in schools. [16] This utilized classroom-suitable HEPA air filters[16] specifically adapted to maximize flow while minimizing noise.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve maximum effectiveness with an acceptable noise level (52db), custom modification was made to get a dust-free air delivery rate (CADR) of 106 ft[3]/min (CFM). The air filtration system is designed for rooms up to 400 ft,[2] was effective in reducing particles in our Pilot (4 filters/classroom),[16] and was well-received in the classroom/school setting.…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is opportunity for environmental intervention studies outside of the home. Jhun et al(78) demonstrated that classroom-based air cleaners led to significant reductions in PM 2.5 and black carbon when compared to control classrooms. This highlights the school as a location for future environmental intervention studies aimed at improving asthma in children.…”
Section: Asthma and The Environmentmentioning
confidence: 99%
“…(61) Other than replacement of gas stoves with electric stoves, fewer methods are currently available for indoor NO 2 reduction of indoor or outdoor origin. (62, 63) In homes with smokers, recent home and school-based intervention trials in children report significant reductions in particulate matter with HEPA filter use, (6466) but without reduction in indoor gases, without consistent reductions in markers of cigarette smoke, and with mixed success in improving child asthma symptoms. The efficacy in reducing indoor pollutants is dependent on room dimensions and building structure and conditions.…”
Section: Introductionmentioning
confidence: 99%